2019
DOI: 10.3390/ma12244180
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Silver Nanoparticle Synthesis by Escherichia Coli Transformed with Candida Albicans Metallothionein Gene

Abstract: In this study, the metallothionein gene of Candida albicans (C. albicans) was assembled by polymerase chain reaction (PCR), inserted into pUC19 vector, and further transformed into Escherichia coli (E. coli) DH5α cells. The capacity of these recombinant E. coli DH5α cells to synthesize silver nanoparticles was examined. Our results demonstrated that the expression of C. albicans metallothionein in E. coli promoted the bacterial tolerance to metal ions and increased yield of silver nanoparticle synthesis. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 26 publications
(72 reference statements)
0
10
0
Order By: Relevance
“…E. coli was also reported to form different metallic nanoparticles, including silver, gold, copper, iron, etc. [20,21]. We incubated the supernatant of 24 h grown culture of P. putida and E. coli with silver salt for the next 24-48 h. The extracellular supernatant helped in the reduction of the silver salt to nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…E. coli was also reported to form different metallic nanoparticles, including silver, gold, copper, iron, etc. [20,21]. We incubated the supernatant of 24 h grown culture of P. putida and E. coli with silver salt for the next 24-48 h. The extracellular supernatant helped in the reduction of the silver salt to nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…DH5α is commonly used laboratory E. coli strain to maintain and amplify small plasmid DNA [43]. More importantly, it is often used in fundamental research of a wide range of new potential antibacterials [44][45][46][47] and even for the production of silver nanoparticles upon transformation [48]. Additionally, it seemed reasonable to model growth curves of this strain since we have thoroughly investigated its growth parameters [40].…”
Section: Minimal Inhibitory and Bactericidal Concentrationsmentioning
confidence: 99%
“…Recently, Yuan et al, 2019 also reported the fabrication of AgNPs by using a transformed strain of E. coli containing metallothionein in the gene from Candida albicans . The authors concluded that the transformed E. coli can be further used for the enhanced production AgNPs [ 78 ].…”
Section: Strategies For Synthesis Of Nanoparticles Using Microbesmentioning
confidence: 99%